Driving forces of hypermarket's customer loyalty: an empirical study in Malaysia - Nikhashemi, Seyed Rajab; Paim, Laily; Md Sidin, Samsinar; Khatibi, Ali (American-Eurasian Network for Scientific Information, 2014)
Background: Customer satisfaction and loyalty is the output of a successful retail marketing model in a competitive marketing environment, thus creating value for both customers and retailers. Malaysian hypermarkets have experienced marked growth and development in the recent years, with many of these hypermarkets laying special emphasis on the development of customer satisfaction and customer in order to afford the long term tapping of sales revenue. However, in their drive for customer satisfaction, many of these hypermarkets continue to be faced with a number of impediments. These include increasing competition, market analysis and rising customer expectations. Objectives: The aim of this study is to investigate the driving forces of customer loyalty among hypermarket’s customer in Malaysia. With data collected from a Giant, Tesco, Mydin, and Aeon Big customers via non-probability sampling. Results: The study empirically examines the nature of the effect of the customer perceived service quality, quality of product, pricing strategy, store attributes and customer loyalty through the mediating variable of customer satisfaction. However the outcomes revealed that the customer perceived service quality, pricing strategy, quality of product and finally store attributes have significant relationship on customer satisfaction and overall customer satisfaction has strong impact on hypermarket’s customer loyalty, especially, product quality is more significant on customer satisfaction with compare to service quality. Conclusion: This finding confirms the role of customer satisfaction as an important determinant of customer loyalty in the hypermarket customer’s loyalty setting. However this study offered an insight into hypermarket’s customer loyalty from Malaysian customer a perspective which has not previously been investigated.